De-Gendering in the Use of E-Learning - Remmele, Bernd; Holthaus, Matthias (International Review of Research in Open and Distributed Learning, 2013)
The starting point of the paper is the co-construction of gender and technology, that is, the theory that the usage of and the attitude to certain kinds of technology are a way to “do” one’s gender. A survey is presented that supports the assumption that with the routinization of e-learning in higher education e-learning loses its character as a technology, which can be used for gender performance. With the routinization of its usage e-learning is becoming a gender-neutral tool with no outstanding technological appeal. However, though doing gender may disappear in certain fields the co-construction of gender and technology is still valid as basic structure. Furthermore, the results show that e-learning meanwhile supports the attitude we call study as consumption, that is, the expectation that the main e-learning features are usual services to be provided by the educational institution. This attitude is to be found among male and female students alike.